Children's orientation towards sporting events and sporting emotions - Ahmet İslam (Turkish Journal of Kinesiology)
This paper investigated the relationship between middle school students' orientation towards sporting events and their level of sporting emotions. The sample consisted of 212 students from middle schools affiliated with the National Education in Gölbaşı District of Ankara, Türkiye, in the 2022-2023 academic year. Data were collected using a personal information form, the Consumer Orientation towards Sporting Events Scale (COSES), and the Sport Emotion Questionnaire (SEQ). The results show that middle school students' search for anxiety reduction is associated with an increased orientation towards sporting events. There is a positive relationship between students' enjoyment scores and their sport involvement, suggesting that higher enjoyment scores are associated with greater sport involvement. Higher levels of anxiety are associated with higher levels of sport involvement. The increase in their excitement level has a positive effect on their orientation towards sporting events. An increase in their level of happiness has a positive effect on their orientation towards sporting events and thus on their emotions. The correlation matrix showed generally moderate and significant relationships between the scale scores. The psychological constructs of sporting emotions that influence performance in middle school students can be identified and analyzed. When students are aware of their emotions in sport, they are more likely to engage in practices that positively affect their performance. Researchers should conduct evaluations of students' sporting emotions using different psychological constructs to make significant contributions to the field. By exploring different perspectives and approaches, a more comprehensive understanding of the relationship between sporting emotions and student outcomes can be achieved.